2015
DOI: 10.5812/ircmj.30974
|View full text |Cite
|
Sign up to set email alerts
|

Catastrophic Health Expenditure Among Iranian Rural and Urban Households, 2013 - 2014

Abstract: Background:During the last two decades, the trend of out-of-pocket payments (OOP) for health services by Iranian households has been a matter of concern and it has exposed a significant proportion of them to catastrophic and impoverishing health expenditures.Objectives:The current study aimed to investigate three objectives: First, the mean of out-of-pocket payments among Iranian households for health services; second, the headcount and overshoot measures of catastrophic health expenditure; and finally the lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 19 publications
(30 reference statements)
1
37
0
2
Order By: Relevance
“…Several studies have investigated the exposure to catastrophic health expenditures before the implementation of the HTP (before 2014) and found different rates in different years. One study by Ghiasvand et al showed about 2.87% of urban households and 2.45% of rural households have experienced catastrophic health expenditure in 2013 to 2014 . Rates of the exposure to catastrophic health expenditures in 2014 to 2015 were about 4.38% for rural and 2.69% for urban households .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have investigated the exposure to catastrophic health expenditures before the implementation of the HTP (before 2014) and found different rates in different years. One study by Ghiasvand et al showed about 2.87% of urban households and 2.45% of rural households have experienced catastrophic health expenditure in 2013 to 2014 . Rates of the exposure to catastrophic health expenditures in 2014 to 2015 were about 4.38% for rural and 2.69% for urban households .…”
Section: Discussionmentioning
confidence: 99%
“…In Iran, equity in healthcare financing and utilization based on horizontal and vertical equity approaches has been emphasized in national plans, and it is a component of societal preferences. However, results of studies during the last few years showed that the previous and current governments have not been able to achieve these goals . To make some inroads in achieving these goals, in 2014, the Iranian government enacted the “ Health Transformation Plan ” (HTP) with financial protection against catastrophic healthcare expenditure as one of its objectives.…”
Section: Introductionmentioning
confidence: 99%
“…38 Although we found that having basic health insurance coverage significantly reduces the probability of making informal payments, the results of other similar studies have been contradictory. For example, studies by Meskarpour-Amiri et al 22 and Ghiasvand et al 39 have shown that having health insurance coverage does not have any significant effect on avoiding informal payments and catastrophic healthcare expenditures. The differences between the results of the present study and those of the aforementioned studies can be due to the differences in the type of studies and the studied samples.…”
Section: Factors Affecting Informal Paymentsmentioning
confidence: 99%
“…High OOP payment was a major challenge to the people of Iran and many Iranians were unable to afford the cost in seeking for health care due to it (10). Previous studies in Iran have shown that the incidence of catastrophic health expenditures (CHE) ranges from 6% -17.7% at the national level (11,12), and 14.2% -22.2 % at the regional level (13,14), with an OOP payment of about 52.1% (15). To address this challenge, in 2014, the government of Iran took a bold health reform initiative by instituting the health sector evolution plan (HSEP) (16).…”
Section: Introductionmentioning
confidence: 99%